Resource Equivalency Analysis (REA): Implication environmental of groundwater in Kupang East Nusa Tenggara - Aplonia Bani; Suprihatin; SK Saptomo; RL Kaswanto (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2023)
This article discusses the environmental assessment caused by the commercial use of groundwater by the community as landowners. In the future, this practice must receive direction and responsibility from the government as policymakers to prevent and repair environmental damage, especially habitat damage and species in strengthening the principle of "paying for commercial groundwater" with the REA methodology to assess and compensate for environmental damage. This method, developed by the National Oceanographic and Atmospheric Administration (NOAA), uses the scale of remediation required to compensate for past, current and future damage. The compensation approaches are the services approach (or the resources approach) and the valuation approach (the value-to-value and value-to-cost approach). The results show that the change in residential land is 0.16%, or 25 ha. The total area of changed settlement/land built up has decreased the function of land which was originally secondary/logged-over dry land forest to become settlement/land built up. Furthermore, there was a decrease in secondary/logged-over dry land forest to open field of 0.03% or 3.1 ha, so that the total area of secondary/logged-over dry land forest decreased by 0.19% or 28.1 ha.